Synthesis of nanosized copper oxide supported HY zeolite catalyst for photocatalytic decolorization of malachite green [electronic resource] - Mohammad Azrul Hisham Satar, 1987- (2013)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2013